KAJIAN PLACEMAKING RUANG PUBLIK DI KAWASAN STADION TELADAN MEDAN - Ahmad Zulfikar; Kinanti Wijaya; Harry Wibowo; Riansyah Putra; Sarwa (Jurnal Arsitektur ARCADE, 2025)
Abstract: A public space in an urban area is essentially designed for the community so that they can socialize and carry out activities safely and comfortably. The presence of public spaces in large cities, especially, is very important and influences various activities of its residents. Parks and streets are examples of public spaces that are frequently used by the community for various everyday activities. The Teladan Stadium area in Medan City is one such public open space that is widely used by the public for various activities and has become a popular destination. This study aims to assess the extent of the benefits of this public open space using a placemaking approach, based on the criteria of sociability, uses and activities, access and linkage, as well as comfort and image (Bohl, 2002). The results of this study are expected to provide direction and policy recommendations regarding issues in public spaces with a placemaking approach. The research method used is descriptive qualitative with a mapping of public activities through Behaviour Mapping in the Teladan Stadium area in Medan, in order to determine the extent of placemaking and efforts to transform space into a place used for activities in that area. Keyword: Public space, Placemaking, Stadion Teladan Area..